2009
DOI: 10.1007/s10482-009-9350-7
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic interactions between garden yeasts and microfungal garden pathogens of leaf-cutting ants

Abstract: We investigate the diversity of yeasts isolated in gardens of the leafcutter ant Atta texana. Repeated sampling of gardens from four nests over a 1-year time period showed that gardens contain a diverse assemblage of yeasts. The yeast community in gardens consisted mostly of yeasts associated with plants or soil, but community composition changed between sampling periods. In order to understand the potential disease-suppressing roles of the garden yeasts, we screened isolates for antagonistic effects against k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 49 publications
(70 reference statements)
1
75
0
4
Order By: Relevance
“…Several other studies with leaf-cutting ants (Atta and Acromyrmex) suggested that Trichoderma fungi are associated with the plant substrate foraged by workers (Barbosa 2004;Rodrigues et al 2008Rodrigues et al , 2009Rodrigues et al , 2011 Samuels et al 2006;Bae et al 2009;Chaverri et al 2011;Druzhinina et al 2012;Bailey and Melnick 2013). Regarding T. viride, this species was considered to be restricted to the north hemisphere and found in soil, trunks and decaying wood, with only two strains reported in the tropics, isolated as endophytes of Theobroma gileri (Ecuador) and Theobroma cacao (Brazil) (Lieckfeldt et al 1999;Jaklitsch et al 2006;Samuels et al 2006).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several other studies with leaf-cutting ants (Atta and Acromyrmex) suggested that Trichoderma fungi are associated with the plant substrate foraged by workers (Barbosa 2004;Rodrigues et al 2008Rodrigues et al , 2009Rodrigues et al , 2011 Samuels et al 2006;Bae et al 2009;Chaverri et al 2011;Druzhinina et al 2012;Bailey and Melnick 2013). Regarding T. viride, this species was considered to be restricted to the north hemisphere and found in soil, trunks and decaying wood, with only two strains reported in the tropics, isolated as endophytes of Theobroma gileri (Ecuador) and Theobroma cacao (Brazil) (Lieckfeldt et al 1999;Jaklitsch et al 2006;Samuels et al 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Since the first report of Trichoderma in colonies of leaf-cutting ants (Kreisel 1972), several studies reported the occurrence of this genus in colonies of these insects (Barbosa 2004;Poulsen and Currie 2006;Rodrigues et al 2008Rodrigues et al , 2009Augustin 2011;Rodrigues et al 2014). However, none of these studies used a detailed taxonomic approach to identify Trichoderma species that occur in this environment.…”
Section: The Authors Also Suggested Cunninghamella Elegans Syncephalmentioning
confidence: 99%
“…This region is generally used as the molecular marker for yeast identification (Kurtzman and Robnett, 1998;Schoch et al, 2012). PCR conditions were as follows: 96°C for 3 min, 35 cycles at 96°C for 30 s, 61°C for 45 s, and an extension step at 72°C for 1 min (Rodrigues et al, 2009). The expected size of amplicons (500-600 base pairs) were checked after electrophoresis in 1% agarose gel supplemented with GelRed ® (Biotium).…”
Section: Identification Of Selected Strainsmentioning
confidence: 99%
“…This possibility was raised when T. septentrionalis and Trachymyrmex turrifex experienced fitness reductions after adopting Attamyces fungus (Seal and Mueller, 2014), which apparently was the result of invasion by weedy fungi destroying gardens, though the exact mechanism of garden decline was not known with certainty in that study. Trachymyrmex arizonensis likely associate with different microbial communities that are distinct from other species of Trachymyrmex, as do other attine species Rodrigues et al, 2011;Sen et al, 2009), which may or may not be able to withstand invasions by competitor fungi (Haeder et al, 2009;Mueller, 2012;Rodrigues et al, 2009). Another non-exclusive possibility is that ants may not apply the appropriate triggers to novel fungal symbionts that would stimulate the synthesis of the diverse enzymatic machinery required for the metabolism of carbohydrates, lignocelluloses and proteins that Attamyces is known to possess (Aylward et al, 2013).…”
Section: Research Articlementioning
confidence: 99%